Associations between training characteristics and change in peak oxygen consumption following exercise training in patients with heart failure with preserved ejection fraction. (3rd October 2022) - Mueller, S; Cervenka, M; Winzer, E B; Gevaert, A B; Fegers-Wustrow, I; Haller, B; Edelmann, F; Christle, J W; Haykowsky, M J; Linke, A; Adams, V; Pieske, B; et al.
Abstract: Introduction: In heart failure with preserved ejection fraction (HFpEF), moderate continuous training (MCT) and high-intensity interval training (HIIT) are both effective in increasing peak oxygen uptake (peak V̇O2 ). Purpose: The aim of this study was to investigate the association of training characteristics (i.e. average sessions/week, average duration/week, mean intensity) and change in peak V̇O2 following 3 months of MCT and HIIT in patients with HFpEF. Methods: Among 120 patients who were randomized to MCT (5x40 min/week at 35–50% heart rate reserve [HRR]) or HIIT (3x38 min/week at 80–90% HRR), those who completed 3-month follow-up (N=107) were considered for this analysis. Training duration and heart rates [HR] were recorded with a smartphone application, evaluated with a customized software and manually checked for plausibility. If HR measurements were classified as invalid/unreliable (e.g. very strong fluctuations), patients were excluded from analysis. Intensities were calculated as average % HRR of total sessions in MCT and the average of the highest % HRR values of all intervals in HIIT. Associations between training characteristics and change in peak V̇O2 were evaluated using univariate and multivariate regression analyses. Individual HR-V̇O2 relationships were used to calculate and compare energy expenditure (MET-minutes) in MCT and HIIT. Results: After excluding 16 patients due to invalid/unreliable HR data, 91 patients (67% female, 69±7 years) were included in this analysis. On average, MCT patients (N=45) performed 4.0±1.2 sessions/week (162±52 min/week) at 47.4±6.7% HRR, while HIIT patients (N=46) performed 2.4±0.8 sessions/week (96±40 min/week) at 81.8±11.8% HRR. Peak V̇O2 was improved by 1.70±2.35 ml/kg/min in MCT and 1.46±2.98 ml/kg/min in HIIT (difference: 0.24 [95% CI, −0.87 to 1.34], p=0.67). The associations between training characteristics and change in peak V̇O2 are shown in Fig.1. Mean % HRR was not significantly associated with the change in peak V̇O2 in the HIIT group, whereas in MCT, mean duration/week and mean intensity were of similar relative importance (standardized coefficients) and explained up to 26% of the variation in change in peak V̇O2 (Table 1). Average weekly MET-minutes above rest were 451±260 for MCT and 389±375 for HIIT (difference: 62 [95% CI, −71 to 195], p=0.36). After adjustment for MET-minutes, the difference in change in peak V̇O2 between groups diminished to 0.09 ml/kg/min (95% CI, −0.97 to 1.16; p=0.98). Conclusions: Weekly duration and mean % HRR had a similar predictive ability for the change in peak V̇O2 following MCT with, interestingly, lower change in peak V̇O2 with increasing intensity. In HIIT, mean % HRR was not significantly associated with the change in peak V̇O2 . After adjusting for energy expenditure, the difference in change in peak V̇O2 between training modes diminished, suggesting that MCT and HIIT were similarly effective. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Commission, Framework Program 7